The Determinant Factors of Capital Structure in Cyclical Sector: Empirical Study from Indonesia - Heru Cahyo; Siti Muntahanah; Sodik Dwi Purnomo (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to test seven internal factors determining capital structure using trade-off theory in the consumer cyclical sector in Indonesia. The research sample used a purposive sampling of 15 companies with 225 observations. Generalized Method of Moment analysis method for panel data. The research found that significant firm growth and size were proven. Tangible assets, non-debt tax shield, growth opportunity, and significant earning volume were not proven, and profitability was not significant. Investors can make the right decisions regarding ownership of company shares to sell or buy. In addition, potential investors can invest their funds by considering the company's high debt costs, which results in financial distress costs. The findings provide an overview for company managers in making decisions to achieve an optimal capital structure.